2022
DOI: 10.1002/hyp.14514
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater‐stream connectivity from minutes to months across United States basins as revealed by spectral analysis

Abstract: Stream corridors are dynamic places where streams and aquifers are connected and interact to various degrees, depending on geology, climate, stream morphology, and water use. Water table fluctuations propagate through the unconfined aquifer and are linked with changes in solute export to streams and biogeochemical transformations in floodplain soils. Through publicly available USGS data, this study aims to better understand the behaviour of stream‐groundwater connectivity and water table fluctuations by analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Cui et al [29] applied wavelet analysis to investigate the response relationship of groundwater depth to precipitation based on the monthly time series data and found that the delayed response time ranged from 8 to 14 months in Baotou, China during the period of 2007-2017. Clyne and Sawyer analyzed the lag response time of riparian groundwater level to stream stage at 17 locations distributed in the United States and found that it varied from days to weeks in the spring and summer [30]. Qi studied the dynamic response of karstic water level to precipitation and water stage of the Yellow River in Jinan area of Shandong Province in China during 2007-2018 [31].…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al [29] applied wavelet analysis to investigate the response relationship of groundwater depth to precipitation based on the monthly time series data and found that the delayed response time ranged from 8 to 14 months in Baotou, China during the period of 2007-2017. Clyne and Sawyer analyzed the lag response time of riparian groundwater level to stream stage at 17 locations distributed in the United States and found that it varied from days to weeks in the spring and summer [30]. Qi studied the dynamic response of karstic water level to precipitation and water stage of the Yellow River in Jinan area of Shandong Province in China during 2007-2018 [31].…”
Section: Introductionmentioning
confidence: 99%